IMPLEMENTASI TRIPLE HELIX MENINGKATKAN HASIL PRODUKSI KRUPUK UMKM DI KECAMATAN KREMBUNG KABUPATEN SIDOARJO - Khusniyah Khusniyah (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2019)
Abstract Triple Helix is a synergy of strengths between academics, business and government. Academics with resources, science and technology focus on producing a variety of applicable findings and innovations. Business circles capitalize which provides economic benefits and benefits for the community. The government guarantees and maintains the stability of their relations with conducive regulation. This study uses non-probability sampling, namely purposive sampling with the provisions that: (1) receive assistance from the government and the university (both); (2) receive assistance from one of the government or the university, as the implementation of the Triple Helix program. received assistance from the Government and the University experiencing an increase in production by 17% -19% while SME that only received assistance from one (from the Government or University) experienced a production increase of 14% -16%. Keywords: Triple Helix, government, universities and SME